Spiny-cheek crayfish Orconectes limosus carry a novel genotype of the crayfish plague pathogen Aphanomyces astaci - Kozubíková, Eva; Viljamaa-Dirks, Satu; Heinikainen, Sirpa; Petrusek, Adam (Journal of invertebrate pathology, 2011)
The oomycete Aphanomyces astaci causes mass mortalities of European crayfish. Different species of North American crayfish, original hosts of this parasite, seem to carry different strains of A. astaci. So far, four distinct genotype groups have been recognised using Random Amplification of Polymorphic DNA (RAPD-PCR). We succeeded in isolating A. astaci from the spiny-cheek crayfish Orconectes limosus, a widespread invader in Europe, and confirmed that this species carries a novel A. astaci genotype. Improving knowledge on the diversity of this parasite may facilitate identification of genotypes in mass mortalities of European crayfish, thus tracing the sources of infection.
Keywords: Random Amplified Polymorphic DNA Technique; infekce; interakce hostitele a patogenu; genetická variace; Genotype; Species Specificity; fylogeneze; druhová specificita; DNA, Fungal; DNA fungální; zvířata; severní raci; technika náhodné amplifikace polymorfní DNA; Animals; Aphanomyces; genotyp; Host-Pathogen Interactions; Infections; Astacoidea; Phylogeny; Genetic Variation